The involvement of RNA N6‐methyladenosine and histone methylation modification in decidualization and endometriosis‐associated infertility - Xiang Lin; Yongdong Dai; Weijia Gu; Yi Zhang; Feng Zhuo; Fanxuan Zhao; Xiaoying Jin; Chao Li; Dong Huang; Xiaomei Tong; Songying Zhang (Clinical and Translational Medicine, 2024)
Abstract Defective decidualization of endometrial stromal cells (ESCs) in endometriosis (EM) patients leads to inadequate endometrial receptivity and EM‐associated infertility. Hypoxia is an inevitable pathological process of EM and participates in deficient decidualization of the eutopic secretory endometrium. Enhancer of zeste homology 2 (EZH2) is a methyltransferase which catalyses H3K27Me3, leading to decreased expression levels of target genes. Although EZH2 expression is low under normal decidualization, it is abundantly increased in the eutopic secretory endometrium of EM and is induced by hypoxia. Chromatin immunoprecipitation‐PCR results revealed that decidua marker IGFBP1 is a direct target of EZH2, partially explaining the increased levels of histone methylation modification in defected decidualization of EM. To mechanism controlling this, we examined the effects of hypoxia on EZH2 and decidualization. EZH2 mRNA showed decreased m6A modification and increased expression levels under hypoxia and decidualization combined treatment. Increased EZH2 expression was due to the increased expression of m6A demethylase ALKBH5 and decreased expression of the m6A reader protein YTHDF2. YTHDF2 directly bind to the m6A modification site of EZH2 to promote EZH2 mRNA degradation in ESCs. Moreover, selective Ezh2 depletion in mouse ESCs increased endometrial receptivity and improved mouse fertility by up‐regulating decidua marker IGFBP1 expression. This is the first report showing that YTHDF2 can act as a m6A reader to promote decidualization by decreasing the stability of EZH2 mRNA and further increasing the expression of IGFBP1 in ESCs. Taken together, our findings highlight the critical role of EZH2/H3K27Me3 in decidualization and reveal a novel epigenetic mechanism by which hypoxia can suppress EM decidualization by decreasing the m6A modification of EZH2 mRNA.